2019
DOI: 10.1002/pmrj.12148
|View full text |Cite
|
Sign up to set email alerts
|

Simulation‐Based Education for Urgent Medical Complications Common to the Rehabilitation Setting: An Educational Program for Physical Medicine and Rehabilitation Residents

Abstract: Background: Simulation technology is being increasingly adopted into medical education and is consistently associated with positive effects on knowledge, skills, and patient-related outcomes. There is little evidence on the use of simulation technology for the instruction of urgent medical complications to physical medicine and rehabilitation (PM&R) residents. Objective: To examine whether a simulation-based educational program can improve PM&R resident confidence and knowledge in the assessment and management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…However, the rating is modest overall (3.2 out of 5), suggesting that the confidence remains proportional to the role and skill level of a medical student. Prior studies have shown similar improvement in confidence following in-person simulations [6][7][8]. However, this is the first to the authors' knowledge to replicate an improvement in confidence utilizing virtual simulation.…”
Section: Implications Of the Educational Interventionmentioning
confidence: 51%
See 1 more Smart Citation
“…However, the rating is modest overall (3.2 out of 5), suggesting that the confidence remains proportional to the role and skill level of a medical student. Prior studies have shown similar improvement in confidence following in-person simulations [6][7][8]. However, this is the first to the authors' knowledge to replicate an improvement in confidence utilizing virtual simulation.…”
Section: Implications Of the Educational Interventionmentioning
confidence: 51%
“…Formal training in behavioral emergencies is not standardized, particularly for medical students, and few targeted educational interventions have been studied. The limited literature available has shown that simulations are effective at improving confidence and competence among students and trainees [6][7][8][9]. In particular, simulated patient encounters involving agitated individuals can foster teamwork and help learners address the safety of both patients and staff [9,10].…”
mentioning
confidence: 99%
“…54 Rehabilitation residents’ knowledge on urgent care improved from the baseline mean score of 57.8% to 85% after the educational course consisting of didactic lecture and HFS. 57 A larger number of studies investigate the effects of HFSs independently and demonstrate substantial score improvement from pre-simulation to post-simulation tests. This has been proven in diverse clinical disciplines, where simulations improved test scores in paramedic seizure management by 26%, 58 increased medical students’ competencies in managing neurological emergencies after simulations, 59 and enhanced safe drug administration in nursing students.…”
Section: Resultsmentioning
confidence: 99%
“…In all healthcare disciplines, the use of simulation is becoming the new norm for training and testing knowledge. Some research has shown it is more engaging for those persons being taught (Malmut & Rho, 2019; Silva et al, 2017). Simulation-based learning has been shown to be effective in teaching patients with SCI and families about clean catheterization and sexuality (Hencklein et al, 2021; Le Danseur et al, 2018).…”
Section: Discussionmentioning
confidence: 99%